2022
DOI: 10.1037/dev0000942
|View full text |Cite
|
Sign up to set email alerts
|

Altruism, hypocrisy and theory of mind in autistic and nonautistic children.

Abstract: Children make choices between generosity and greed every day. Often they must also choose between confession or denial of antisocial acts like greed, thereby displaying either honesty or hypocrisy. Such choices pose cognitive challenges that, in theory, might reflect children’s developing social-cognitions and affect their daily social lives and developmental opportunities. Individual differences in altruism and hypocrisy were examined in relation to theory of mind (ToM) in 102 school-age children (44 autistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A study of children with and without ASD found a similar result, where the behavioral difference between ASD and neurotypical children was greater when the donation recipient was absent (Paulus & Rosal‐Grifoll, 2017). Research by Peterson and Wellman (2022) also demonstrated less social orienting in children with ASD as they exhibited less hypocrisy; that is, less discrepancy between their reported donation preferences (where high donation preferences are socially desirable and uncostly) and their actual donations (where donating more is socially desirable, but also more costly). Tei and colleagues (Tei et al, 2019) found more consistent social discounting behavior in ASD than in neurotypical adults, being less influenced by social distance to the recipient.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study of children with and without ASD found a similar result, where the behavioral difference between ASD and neurotypical children was greater when the donation recipient was absent (Paulus & Rosal‐Grifoll, 2017). Research by Peterson and Wellman (2022) also demonstrated less social orienting in children with ASD as they exhibited less hypocrisy; that is, less discrepancy between their reported donation preferences (where high donation preferences are socially desirable and uncostly) and their actual donations (where donating more is socially desirable, but also more costly). Tei and colleagues (Tei et al, 2019) found more consistent social discounting behavior in ASD than in neurotypical adults, being less influenced by social distance to the recipient.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, a recent study that examined prosocial behavior (donating self‐relevant items) and hypocrisy (the difference between one's reported hypothetical donation preferences and actual donations when able to donate the actual items) in children found a different result (Peterson & Wellman, 2022). There was a trend toward more prosocial behavior in the form of self‐relevant items given away to an unknown peer, and a significant effect of less hypocrisy (less discrepancy between costly and uncostly prosocial behaviors) in ASD, relative to non‐ASD children.…”
Section: Introductionmentioning
confidence: 91%
“…The stickers that the actor kept were put in white envelopes, while the stickers given to others were put in blue envelopes. The results indicated that both autistic and neurotypical children demonstrated altruistic tendencies ( Peterson and Wellman, 2022 ). (E) The red figure represented the actor, the black figure at the table represented the experimenter, and the other black figure was the bystander of the same age as the actor.…”
Section: Why Help Others: Concern For Othersmentioning
confidence: 99%
“…The results showed that toddlers would help their friends more, but would also help their peers who were not their friends. Peterson and Wellman (2022) studied 102 school-age children, and the experimenter gave them 10 pieces of stickers they liked most, which allowed them to freely control and keep or give to others. The ones kept by themselves were put in white envelopes, and the ones given to others were put in blue envelopes ( Figure 3D ).…”
Section: Why Help Others: Concern For Othersmentioning
confidence: 99%